2011
DOI: 10.1007/s12892-010-0102-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative potential of phenotypic, ISSR and SSR markers for characterization of sesame (Sesamum indicum L.) varieties from India

Abstract: The assessment of genetic diversity is a primary concern of plant breeders and germplasm curators for which morphological traits are internationally accepted descriptors but are often associated with limitations due to G x E interactions. Phenotypic, ISSR, and SSR markers were employed to determine the genetic diversity and relationships among 20 commercially cultivated sesame genotypes representing different geographical regions of India. A narrow range of genetic dissimilarity (0.01 -0.12) with mixed cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 28 publications
1
20
4
Order By: Relevance
“…Each marker amplified 1 to 5 alleles with an average of 2.89 alleles per locus. The SSR markers in the present study showed a lower number of alleles than previous analysis of the diversity of sesame accessions conducted with SSR markers (Dixit et al, 2005;Gebremichaeland Parzies, 2011;Kumar and Sharma, 2011;Nweke et al, 2015;Pandey et al, 2015).…”
Section: Resultscontrasting
confidence: 78%
See 1 more Smart Citation
“…Each marker amplified 1 to 5 alleles with an average of 2.89 alleles per locus. The SSR markers in the present study showed a lower number of alleles than previous analysis of the diversity of sesame accessions conducted with SSR markers (Dixit et al, 2005;Gebremichaeland Parzies, 2011;Kumar and Sharma, 2011;Nweke et al, 2015;Pandey et al, 2015).…”
Section: Resultscontrasting
confidence: 78%
“…These 27 SSR primers produced 78 bands of which 49 were polymorphic (62.82%). The level of polymorphism obtained in this study (62.82%) was low compared with the previous study in which a high level of polymorphism was detected among Indian sesame genotypes were more than 73% (Kumar and Sharma, 2011). Each marker amplified 1 to 5 alleles with an average of 2.89 alleles per locus.…”
Section: Resultscontrasting
confidence: 76%
“…Although several reports have highlighted a higher level of genetic variation generated with SSR primers compared to ISSR primers 2009;Kumar and Sharma, 2011;Hamza et al, 2013) the present study revealed that ISSR markers were useful in differentiating D. cespitosa populations growing in regions with different levels of heavy metals. The levels of polymorphic loci generated with ISSR and of observed heterozygosity obtained with SSR weremoderate to high.…”
Section: Resultscontrasting
confidence: 55%
“…As a result, microsatellites are considered as ideal markers for forensic identification, paternity analysis, gene mapping, plant breeding, conservation biology and population genetics (Buschiazzo and Gemmell, 2006;Gupta et al, 1996;Kumar and Sharma, 2011;Mehes et al, 2007;2009;Hamza et al, 2013;Peakall et al, 1998;Simpson et al, 2013).…”
Section: Ssr Markersmentioning
confidence: 99%
See 1 more Smart Citation